Normalization of Corruption and the Erosion of Shame: A Legal Sociological Review of the Culture of Impunity in Indonesia - Mesra, Romi (PT. NALURI EDUKASI PRESS, 2024)
This research aims to analyze the loss of shame among perpetrators of corruption in Indonesia and its relationship to the culture of impunity and the ineffectiveness of punishment from the perspective of legal sociology. This study uses a descriptive qualitative approach with a literature study method on academic documents, research reports, and current news. The analysis was carried out using content analysis and critical interpretation of secondary data. The results of the study indicate that shame as a social sanction no longer functions in corruption cases due to the weak social reaction and tolerance of society towards deviant elites. On the other hand, the inconsistent and often symbolic legal system fails to have a deterrent effect on perpetrators. The culture of impunity that occurs systematically causes the delegitimization of law in the eyes of the public. This article emphasizes the need for a more holistic legal approach based on the reconstruction of social values ​​so that corruption is no longer a practice that is normally accepted in public life.